ETNOMATEMATIKA PADA KAIN TENUN LIPA KAET - Aida Puji Rahayu; Melfi Snae; Stepanus Bani (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
The Indonesian education curriculum requires cultural involvement in learning process, with the aim that students can become generation that have character to preserve culture as the foundation of national character. Mathematical studies in culture are known as ethnomathematics. Ethnomathematics raises cultural wisdom as a mathematics learning resource that can motivate students in the learning process. One of the ethnomathematics objects is woven fabric. The various woven fabric motifs from each region are related to mathematics. One of them is the motif of Lipa Kaet fabric which is originating from the Riung area, Ngada Regency, East Nusa Tenggara, Indonesia. This study aims to explore mathematical concepts that exist in the Lipa Kaet fabric from the Riung area, East Nusa Tenggara, Indonesia. This study uses a qualitative method with an ethnographic approach. Data collection techniques used are documentation, observation and interview. The analysis used is descriptive analysis so that it can present information about the relevance of mathematics and culture. According to the results of the study, it can be concluded that there is a relationship between Lipa Kaet motifs and mathematics which is the concept of two dimensional-figure such as rectangular, rhombic, triangular and hexagonal. The motif can be used as a mathematics learning medium especially for junior high school students for the concept of two dimensional-figure.